Fe-doped ZnIn2S4 photocatalyst as well as preparation method and application thereof

The Fe-doped ZnIn2S4 photocatalyst is synthesized by hydrothermal method, and the Fe-doping of non-precious metals is used to solve the problem of increasing costs using precious metals in the prior art, and the efficient and economical photocatalytic hydrogen production effect is achieved.

CN119657175AActive Publication Date: 2025-03-21NANCHANG HANGKONG UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411827530.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The prior art mostly uses methanol or ethanol as solvents, and the ZnIn2S4 photocatalyst is usually doped with precious metal elements, which increases the cost.

Method used

The Fe-doped ZnIn2S4 photocatalyst was synthesized by hydrothermal method, using zinc source, indium source, sulfur source and ferrous source as the reaction reagent, and ferrous source as the doping reagent. Fe is a non-precious metal and the doping content is a trace amount.

Benefits of technology

The synthesis of ZnIn2S4 under relatively mild and simple synthetic conditions was achieved, reducing costs, and improving the efficiency of photocatalytic hydrogen production through the introduction of Fe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657175A_ABST
    Figure CN119657175A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalytic nano semiconductor material synthesis, and discloses a Fe-doped ZnIn2S4 photocatalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing a zinc source, an indium source, a sulfur source and a ferrous source with water, and carrying out hydrothermal reaction to obtain the Fe-doped ZnIn2S4 photocatalyst. Fe belongs to non-noble metal, and the doping content of Fe is trace; in addition, the hydrothermal method can be used for synthesizing ZnIn2S4 under the condition of relatively mild and simple synthesis conditions. The prepared non-noble metal doped ZnIn2S4 is used as a photocatalyst for hydrogen production, a new method is provided for solving the problems of energy shortage and environmental pollution, and other possibilities are provided for synthesizing a green, economical, efficient and universal photocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of synthesis of photocatalytic nano-semiconductor materials, in particular to a Fe-doped ZnIn 2 S 4 Photocatalyst and its preparation method and application. Background Art

[0002] Nowadays, energy crisis and environmental pollution are two major challenges facing society, mainly due to the widespread use of fossil fuels. The non-renewable and pollution problems of fossil fuels are in conflict with the sustainable development of society. Hydrogen energy, as a zero-pollution, high-energy-value clean energy, may undertake this historical mission. Hydrogen energy can help humans decarbonize, fix carbon, and even achieve negative carbon. For terminal energy use, hydrogen can be used as the main energy source. It is an important carrier for energy terminals to achieve green and low-carbon transformation. Through the hydrogen-electricity complementary system, carbon dioxide emissions in the industrial energy field can be reduced; in transportation and other aspects, replacing diesel, gasoline and other energy sources with hydrogen energy can also achieve emission reductions, or even "zero emissions". This plays an important role in promoting the realization of the "dual carbon" goal.

[0003] There are many methods for producing hydrogen, such as hydrogen production from fossil raw materials, hydrogen production from water electrolysis, hydrogen production from biomass, photochemical hydrogen production, thermochemical hydrogen production, and solar photocatalytic water decomposition to produce hydrogen. Among them, photocatalytic hydrogen production technology is a promising green hydrogen production route. Compared with other hydrogen production technologies, photocatalytic hydrogen production technology has simpler equipment and fewer components, so it has lower costs. ZnIn 2 S 4 It is a visible light activated ternary metal sulfur photocatalyst with excellent performance. 2 S 3 or CdS), ZnIn 2 S 4 It has a narrower band gap and does not contain toxic metal ions. 2 S 4 The raw materials are widely available. Compared with other ternary metal chalcogenides (such as CuGaS 2 or Zn 3 In 2 S 6 ) is simpler to prepare. Therefore, ZnIn has broad application prospects. 2 S 4 It has attracted extensive attention from researchers in the field of photocatalysis.

[0004] Currently, ZnIn is synthesized by hydrothermal and solvothermal methods. 2 S 4Usually N,N-dimethylformamide (DMF), ethylene glycol (EG), methanol or ethanol are used as solvents. Due to the high reducing properties of methanol or ethanol, they are widely used in the synthesis of ZnIn 2 S 4 In the process, S will be reduced, and the cation doped ZnIn 2 S 4 Mainly in the field of precious metals, this has increased the cation doping of ZnIn 2 S 4 The synthesis cost. Summary of the invention

[0005] The object of the present invention is to provide a Fe-doped ZnIn 2 S 4 Photocatalyst and its preparation method and application solve the problem that the existing technology mostly uses methanol or ethanol as solvent and in the preparation of ZnIn 2 S 4 Photocatalysts are usually doped with precious metal elements, which increases the cost.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a Fe-doped ZnIn 2 S 4 The method for preparing a photocatalyst comprises the following steps:

[0008] The zinc source, indium source, sulfur source, ferrous source and water are mixed and subjected to hydrothermal reaction to obtain Fe-doped ZnIn 2 S 4 Photocatalyst.

[0009] Preferably, in the preparation method, the zinc source includes zinc acetate, zinc chloride, zinc nitrate or zinc sulfate, the indium source includes indium chloride, indium nitrate or indium sulfate, the sulfur source includes thioacetamide or thiourea, and the ferrous source includes ferrous sulfate, ferrous nitrate or ferrous chloride.

[0010] Preferably, in the preparation method, the molar ratio of the zinc source, the indium source and the sulfur source is 1:2:4 to 1:2:8;

[0011] The ratio of the molar amount of the zinc source to the volume of the water is 0.8 mmol:50-80 mL.

[0012] Preferably, in the preparation method, the molar ratio of the zinc source to the ferrous source is 0.8:0.00055-1.12.

[0013] Preferably, in the preparation method, the temperature of the hydrothermal reaction is 120 to 180° C., and the time of the hydrothermal reaction is 12 to 36 hours.

[0014] Preferably, in the preparation method, the hydrothermal reaction further comprises: centrifugation, washing, and freeze-drying in sequence.

[0015] Preferably, in the preparation method, the washing reagents are ethanol and water, and the number of washings using ethanol and the number of washings using water are independently 2 to 3 times;

[0016] The freeze-drying time is 12 to 24 hours.

[0017] Preferably, in the preparation method, the zinc source, indium source, sulfur source, ferrous source and water are mixed in the following manner: the zinc source, indium source, sulfur source and water are first mixed; the mixed solution obtained by the first mixing is second mixed with the ferrous source;

[0018] The first mixing time is 2 to 2.5 hours;

[0019] The second mixing time is 30 to 45 minutes.

[0020] The present invention also provides a Fe-doped ZnIn prepared by the preparation method. 2 S 4 Photocatalyst.

[0021] The present invention also provides a Fe-doped ZnIn 2 S 4 Application of photocatalysts in photocatalytic hydrogen production.

[0022] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) This paper proposes a simple hydrothermal method for interstitial doping to synthesize Fe-doped ZnIn 2 S 4 The preparation method of the nanosheets uses a zinc source (zinc acetate, etc.), an indium source (indium chloride, etc.), a sulfur source (thioacetamide, etc.) and a ferrous source (ferrous sulfate, etc.) as reaction reagents, wherein the ferrous source is used as a doping reagent. In this preparation method, Fe is a non-precious metal, and its doping content is trace; and the hydrothermal method can synthesize ZnIn under relatively mild and simple synthesis conditions. 2 S 4 .ZnIn 2 S 4 As a hydrogen collector, it can absorb water molecules and split them to produce H* that accumulates on ZnIn 2 S 4 The addition of Fe causes surface plasmon resonance, which affects the ZnIn 2 S 4The charge density of S on the surface causes H* to migrate from the S surface to the Fe surface, where it collides to produce H 2 Therefore, the non-noble metal doped ZnIn prepared by the present invention 2 S 4 As a photocatalyst for hydrogen production, it has groundbreaking significance for the synthesis of semiconductor nanomaterials, provides a new method for solving energy shortages and environmental pollution, and offers other possibilities for the synthesis of green, economical, efficient and universal photocatalysts.

[0024] (2) The raw materials of the present invention are easy to obtain and have low cost. 2 S 4 The photocatalytic method is simple, the reaction is easy to operate, the reaction time is short, and large-scale industrial production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0026] Figure 1 Fe-doped ZnIn 2 S 4 Schematic diagram of the preparation process of photocatalyst;

[0027] Figure 2 The XRD diagrams of the photocatalysts obtained in Examples 1 to 3 and Comparative Example 1;

[0028] Figure 3 The hydrogen production results of the photocatalysts obtained in Examples 1 to 3;

[0029] Figure 4 The hydrogen production results of the photocatalysts obtained in Examples 4 to 6;

[0030] Figure 5 The XRD diagrams of the photocatalysts obtained in Examples 7 to 9 and Comparative Example 1;

[0031] Figure 6 The XRD diagrams of the photocatalysts obtained in Comparative Examples 1 to 5;

[0032] Figure 7 To prepare ZnIn in water 2 S 4 Schematic diagram of the principle;

[0033] Figure 8 The hydrogen production results of the photocatalysts obtained in Examples 2, 5, and 10-14 are shown. DETAILED DESCRIPTION

[0034] The present invention provides a Fe-doped ZnIn2 S 4 The method for preparing a photocatalyst comprises the following steps:

[0035] The zinc source, indium source, sulfur source, ferrous source and water are mixed and subjected to hydrothermal reaction to obtain Fe-doped ZnIn 2 S 4 Photocatalyst.

[0036] In the present invention, the method of mixing the zinc source, indium source, sulfur source, ferrous source and water is preferably as follows: first mixing the zinc source, indium source, sulfur source and water; and second mixing the mixed solution obtained by the first mixing with the ferrous source.

[0037] In the present invention, the first mixing time is preferably 2 to 2.5 hours, more preferably 2 to 2.2 hours, and more preferably 2 hours.

[0038] In the present invention, the second mixing time is preferably 30 to 45 minutes, more preferably 30 to 40 minutes, and more preferably 30 minutes.

[0039] In the present invention, the zinc source preferably includes zinc acetate (Zn(CH 3 COO 2 ·2H 2 O), zinc chloride, zinc nitrate (Zn(NO 3 ) 2 6H 2 O) or zinc sulfate (ZnSO 4 7H 2 O), further preferably comprises zinc acetate or zinc chloride, more preferably zinc acetate.

[0040] In the present invention, the indium source preferably includes indium chloride (InCl 3 ·4H 2 O), indium nitrate (In(NO 3 ) 3 ·4H 2 O) or indium sulfate, further preferably indium chloride or indium nitrate, more preferably indium chloride.

[0041] In the present invention, the sulfur source preferably includes thioacetamide (CH 3 CSNH 2 ) or thiourea, more preferably thioacetamide.

[0042] In the present invention, the ferrous source preferably includes ferrous sulfate (FeSO 4 7H 2 O), ferrous nitrate or ferrous chloride, further preferably ferrous sulfate or ferrous chloride, more preferably ferrous sulfate.

[0043] In the present invention, the molar ratio of the zinc source, the indium source and the sulfur source is preferably 1:2:4 to 1:2:8, more preferably 1:2:5.3375 to 1:2:8, and more preferably 1:2:5.3375.

[0044] In the present invention, the molar ratio of the zinc source to the volume of the water is preferably 0.8 mmol:50-80 mL, more preferably 0.8 mmol:55-70 mL, and even more preferably 0.8 mmol:60 mL.

[0045] In the present invention, the molar ratio of the zinc source to the ferrous source is preferably 0.8:0.00055-1.12, more preferably 0.8:0.00055-0.00875, and even more preferably 0.8:0.0011.

[0046] In the present invention, the temperature of the hydrothermal reaction is preferably 120 to 180°C, more preferably 150 to 180°C, and more preferably 180°C.

[0047] In the present invention, the hydrothermal reaction time is preferably 12 to 36 hours, more preferably 18 to 30 hours, and even more preferably 24 hours.

[0048] In the present invention, the hydrothermal reaction preferably further comprises: centrifugation, washing, and freeze-drying in sequence.

[0049] In the present invention, the centrifugal rotation speed is preferably 8000-10000 rpm, more preferably 8000-9000 rpm, and even more preferably 8000 rpm.

[0050] In the present invention, the centrifugation time is preferably 5 to 9 min, more preferably 5 to 7 min, and even more preferably 5 min.

[0051] In the present invention, the washing reagents are preferably ethanol and water.

[0052] In the present invention, the number of times of washing with ethanol is preferably 2 to 3 times, more preferably 2 times.

[0053] In the present invention, the number of times of washing with water is preferably 2 to 3 times, more preferably 3 times

[0054] In the present invention, the freeze-drying atmosphere is preferably a vacuum.

[0055] In the present invention, the freeze-drying time is preferably 12 to 24 hours, more preferably 12 to 18 hours, and more preferably 12 hours.

[0056] The present invention also provides a Fe-doped ZnIn prepared by the preparation method. 2S 4 Photocatalyst.

[0057] The present invention also provides a Fe-doped ZnIn 2 S 4 Application of photocatalysts in photocatalytic hydrogen production.

[0058] In the present invention, the application method is not limited and any method known in the art may be used.

[0059] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] Example 1

[0061] This embodiment provides a Fe-doped ZnIn 2 S 4 Preparation method of photocatalyst (schematic diagram of preparation process as shown in Figure 1 As shown), comprising the following steps:

[0062] Weigh 0.8 mmol Zn(CH 3 COO 2 ·2H 2 O, 1.6mmol InCl 3 ·4H 2 O and 6.4 mmol CH 3 CSNH 2 (TAA) was added into 80 mL of deionized water and stirred for 2 h to obtain a precursor solution;

[0063] Weigh 0.14mmol FeSO 4 7H 2 O was dissolved in the precursor solution and stirred for 30 min;

[0064] The stirred mixed solution was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene and sealed. After heating at 180°C for 24 h, it was naturally cooled to room temperature. The precipitate was centrifuged at 8000 rpm for 5 min, and washed twice with anhydrous ethanol and three times with deionized water. The washed product was freeze-dried under vacuum conditions for 12 h to obtain Fe-doped ZnIn 2 S 4 The photocatalyst is denoted as Fe0.14@ZIS-S6.4.

[0065] Example 2

[0066] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 1 in that: CH 3 CSNH 2 The dosage was modified to 4.27 mmol, and the other parameter conditions were the same as those in Example 1, recorded as Fe0.14@ZIS-S4.27.

[0067] Example 3

[0068] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 1 in that: CH 3 CSNH 2 The dosage was changed to 3.2 mmol, and the other parameters were the same as those in Example 1, recorded as Fe0.14@ZIS-S3.2.

[0069] Comparative Example 1

[0070] This comparative example provides a ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 1 in that: FeSO is removed 4 7H 2 O, and other parameter conditions are the same as those in Example 1, denoted as ZIS or deionized water-ZIS.

[0071] The crystal structures and phases of the photocatalysts obtained in Examples 1 to 3 and Comparative Example 1 were determined by XRD. Figure 2 As shown. Figure 2 It can be seen that all catalysts belong to hexagonal ZnIn 2 S 4 Phase (JCPDS No.65-2023), the characteristic peaks of which are located at 21.55°, 27.50°, 30.38°, 39.56°, 47.15°, 52.37° and 55.45°, respectively, corresponding to {006}, {102}, {104}, {108}, {102}, {110}, {116} and {022} lattice phases. No impurity diffraction peaks were detected in Examples 1 to 3, indicating that the introduction of Fe does not affect the ZnIn 2 S 4 With the increase of S content, the diffraction peak gradually moves toward the small angle direction. When the S content reaches 4.27mmol, the angle shifts to the small angle less, which is related to the Fe doping into ZnIn 2 S 4 is related to the content.

[0072] Example 4

[0073] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 1 in that: FeSO 4 7H 2 The amount of O was changed to 0.07 mmol, and other parameters were the same as those in Example 1, denoted as Fe0.07@ZIS-S6.4.

[0074] Example 5

[0075] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2 The amount of O was changed to 0.07 mmol, and the other parameters were the same as those in Example 2, denoted as Fe0.07@ZIS-S4.27.

[0076] Example 6

[0077] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 3 in that: FeSO 4 7H 2 The amount of O was changed to 0.07 mmol, and the other parameters were the same as those in Example 3, denoted as Fe0.07@ZIS-S3.2.

[0078] Test method for photocatalytic hydrogen production performance:

[0079] The test was conducted in a 150m top exposed and sealed Labsolar-I (AG) (Perfil, China) all-quartz glass automatic online trace gas analysis system. A 300W xenon lamp (PLS-SXE300) equipped with a UV cutoff filter (λ>420nm) was used as the light source and placed 10cm above the reactor. The specific operation process is as follows: 5mg of the photocatalyst sample was weighed and added to 100mL of aqueous solution (containing 0.02mol / L ascorbic acid as a sacrificial agent), and the catalyst was fully dispersed by ultrasound for 1min. Before the hydrogen evolution experiment, argon was purged for 30min to remove the air in the reactor. During the reaction, it was necessary to stir continuously to keep the solution uniform, and the reactor was kept at 10℃ using circulating cooling water. Finally, the amount of gas produced from the sealed quartz reactor every half an hour was measured by gas chromatograph (FLGC.9790I, TCD) to evaluate the hydrogen production performance.

[0080] The above-mentioned photocatalytic hydrogen production performance test method was used to explore the effect of different S contents on hydrogen production. The results are as follows: Figure 3 , Figure 4 As shown in the two figures, it can be seen that when the S content is 4.27 mmol, the hydrogen production is the highest, so the optimal S content is 4.27 mmol.

[0081] Example 7

[0082] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2 The amount of O was changed to 1.12 mmol, and the other parameters were the same as those in Example 2, denoted as Fe1.12@ZIS-S4.27.

[0083] Example 8

[0084] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2 The amount of O was changed to 0.56 mmol, and the other parameters were the same as those in Example 2, denoted as Fe0.56@ZIS-S4.27.

[0085] Example 9

[0086] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2 The amount of O was changed to 0.28 mmol, and the other parameters were the same as those in Example 2, denoted as Fe0.28@ZIS-S4.27.

[0087] The crystal structures and phases of the photocatalysts obtained in Examples 7 to 9 and Comparative Example 1 were determined by XRD. Figure 5 As shown. Figure 5 It can be seen that all catalysts belong to hexagonal ZnIn 2 S 4Phase (JCPDS No.65-2023), the characteristic peaks of which are located at 21.55°, 27.50°, 30.38°, 39.56°, 47.15°, 52.37° and 55.45°, respectively, corresponding to {006}, {102}, {104}, {108}, {102}, {110}, {116} and {022} lattice phases. No impurity diffraction peaks were detected in Examples 7 to 9, indicating that the introduction of Fe does not affect the ZnIn 2 S 4 The crystal structure of Fe 2+ As the content increases, the diffraction peak gradually moves to the direction of small angles and the intercrystalline spacing increases, which is related to the 2+ The ionic radius Greater than Zn 2+ The ionic radius related.

[0088] Comparative Example 2

[0089] This comparative example provides a ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Comparative Example 1 in that deionized water is replaced by methanol, and other parameter conditions are the same as those of Comparative Example 1, and are recorded as methanol-ZIS.

[0090] Comparative Example 3

[0091] This comparative example provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 7 in that deionized water is replaced by methanol, and other parameter conditions are the same as those of Example 7, and are recorded as methanol-Fe1.12@ZIS.

[0092] Comparative Example 4

[0093] This comparative example provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 8 in that deionized water is replaced by methanol, and other parameter conditions are the same as those of Example 8, and are recorded as methanol-Fe0.56@ZIS.

[0094] Comparative Example 5

[0095] This comparative example provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 9 in that deionized water is replaced by methanol, and other parameter conditions are the same as those of Example 9, and are recorded as methanol-Fe0.28@ZIS.

[0096] The crystal structure and phase of the photocatalysts obtained in Comparative Examples 1 to 5 were determined by XRD. Figure 6 As shown. Figure 6 It can be seen that ZnIn synthesized using deionized water 2 S 4 Hexagonal ZnIn 2 S 4 phase (JCPDS No.65-2023), with characteristic peaks located at 21.64°, 27.82°, 30.32°, 39.14°, 47.16°, 52.38° and 56.54°, corresponding to {006}, {102}, {104}, {108}, {102}, {110}, {116} and {022} lattice phases, respectively. ZnIn synthesized using methanol as solvent 2 S 4 The diffraction peak of S single substance was detected (JCPDS No.24-1251), and Fe@ZnIn synthesized using methanol 2 S 4 The diffraction peaks of S element are present in all samples, indicating that S element is produced during the synthesis process due to the high reducing property of methanol.

[0097] The present invention prepares ZnIn in water 2 S 4 The principle is: Figure 7 As shown, in the solution, In 3+ and Zn 2+ Adsorption H 2 O, forming a tetrahedron [In(H 2 O) 4 ] 3+ 、[Zn(H 2 O) 4 ] 2+ and octahedral [In(H 2 O) 6 ] 3+ , and then formed three different complexes with TAA, namely tetrahedral [In(TAA) 4 ] 3+ 、[Zn(TAA) 4 ] 2+ and octahedral [In(TAA) 6 ] 3+ , InS was further formed by stirring 6 、In-S 4 and Zn-S 4 At the same time, these newly generated metal sulfurs further combine in situ to form thermodynamically stable hexagonal ZnIn 2 S 4 Mutually.

[0098] Example 10

[0099] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2 The amount of O was changed to 0.035 mmol, and the other parameters were the same as those in Example 2, denoted as Fe0.035@ZIS-S4.27.

[0100] Embodiment 11

[0101] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2 The amount of O was changed to 0.00875 mmol, and the other parameters were the same as those in Example 2, denoted as Fe0.00875@ZIS-S4.27.

[0102] Example 12

[0103] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2 The amount of O was modified to 0.00219 mmol, and the other parameters were the same as those in Example 2, denoted as Fe0.00219@ZIS-S4.27.

[0104] Embodiment 13

[0105] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2 The amount of O was changed to 0.0011 mmol, and the other parameters were the same as those in Example 2, denoted as Fe0.0011@ZIS-S4.27.

[0106] Embodiment 14

[0107] This embodiment provides a Fe-doped ZnIn 2 S 4 The preparation method of the photocatalyst is different from that of Example 2 in that: FeSO 4 7H 2The amount of O was changed to 0.00055 mmol, and the other parameters were the same as those in Example 2, denoted as Fe0.00055@ZIS-S4.27.

[0108] The above-mentioned test method for photocatalytic hydrogen production performance was used to explore the effect of different Fe contents on hydrogen production. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that when the Fe content continues to increase, the hydrogen production presents a Gaussian distribution, and when the Fe content is 0.0011 mmol, the hydrogen production reaches the highest.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing Fe-doped ZnIn2S4 photocatalyst, characterized in that: The following steps are involved: A zinc source, an indium source, a sulfur source, a ferrous source and water are mixed to carry out a hydrothermal reaction to obtain a Fe-doped ZnIn2S4 photocatalyst.

2. The preparation method according to claim 1, characterized in that: The zinc source includes zinc acetate, zinc chloride, zinc nitrate or zinc sulfate, the indium source includes indium chloride, indium nitrate or indium sulfate, the sulfur source includes thioacetamide or thiourea, and the ferrous source includes ferrous sulfate, ferrous nitrate or ferrous chloride.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the zinc source, the indium source and the sulfur source is 1:2:4 to 1:2:8; The ratio of the molar amount of the zinc source to the volume of the water is 0.8 mmol:50-80 mL.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the zinc source to the ferrous source is 0.8:0.00055-1.

12.

5. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120-180° C., and the time of the hydrothermal reaction is 12-36 hours.

6. The preparation method according to claim 1 or 5, characterized in that: The method further comprises: centrifugation, washing and freeze drying in sequence after the hydrothermal reaction.

7. The preparation method according to claim 6, characterized in that: The washing reagents are ethanol and water, and the number of washings with ethanol and the number of washings with water are independently 2 to 3 times; The freeze-drying time is 12 to 24 hours.

8. The preparation method according to claim 1, characterized in that: The method of mixing the zinc source, the indium source, the sulfur source, the ferrous source and the water is specifically as follows: first mixing the zinc source, the indium source, the sulfur source and the water; second mixing the mixed solution obtained by the first mixing with the ferrous source; The first mixing time is 2 to 2.5 hours; The second mixing time is 30 to 45 minutes.

9. The Fe-doped ZnIn2S4 photocatalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the Fe-doped ZnIn2S4 photocatalyst according to claim 9 in photocatalytic hydrogen production.

Citation Information

Patent Citations

  • Composite photocatalyst MxP / indium zinc sulfide as well as preparation method and application thereof

    CN108620105A

  • Preparation method of Mo or Fe doped Zn1-xIn2S4 catalyst for photocatalytic nitrogen fixation and ammonia synthesis

    CN112264049A

  • Preparation method and application of Z-type alpha-Fe2O3 / ZnIn2S4 composite photocatalyst

    CN114130408A

  • Self-supporting metal element-doped sulfide electrocatalyst and preparation method thereof

    CN116815237A

  • Metal sulfide nano-catalyst as well as preparation method and application thereof

    CN118558330A